The Syrian conflict's impact on international law - Scharf, Michael P., 1963-; Sterio, Milena; Williams, Paul R., 1965- (Cambridge, United Kingdom ; New York, NY, USA Cambridge University Press, 2020)
"Since 2011, Syria has been engulfed in a protracted civil war that began as part of the wave of Arab Spring protests against Middle East tyrants. The Syria conflict has seen the rise and fall of the ISIS terrorist organization, the largest refugee migration since World War II, and the repeated use of chemical weapons against a civilian population. The situation is complicated by the fact that Russia, Syria's long-time ally, has repeatedly used its veto in the U.N. Security Council to prevent the Council from taking actions related to the crisis. With all that, Syria has become a dynamic laboratory for the rapid creation of new international law"--
Prologue -- Introduction -- Historical Background -- Accelerated Formation of Customary International Law -- Use of Force in Self-Defense against Non-State Actors -- Humanitarian Intervention in Response to Use of Chemical Weapons -- Transformation of Accountability Paradigms -- The Syrian Migration Crisis -- International Law and the Syrian Peace Process -- Conclusion -- Appendix : Chautauqua Blueprint for a Syria Tribunal.
Includes bibliographical references and index.
Keywords: Syria -- History -- Civil War, 2011- -- Law and legislation